Non‐Hydrazine Solutions in Processing CuIn(S, Se)2 Photovoltaic Devices from Hydrazinium Precursors. Issue 3 (19th October 2012) - Zhou, Huanping; Hsu, Chia‐Jung; Hsu, Wan‐Ching; Duan, Hsin‐Sheng; Chung, Choong‐Heui; Yang, Wenbing; Yang, Yang
Abstract We report an approach for the fabrication of CuIn(S, Se)2‐based photovoltaic devices from hydrazinium precursors in non‐hydrazine solvents, specifically a ethanolamine/dimethyl sulfoxide (EA/DMSO) mixture. For the first time, both Cu hydrazinium precursor and Cu‐In hydrazinium precursor are found with good solubility in non‐hydrazine solvents, producing molecular‐level blending of metal precursors. Sulfur loss in Cu hydrazinium precursor is compensated for by either introduction of excessive S/Se or the formation of S/Se‐bridged Cu‐In compounds. The success of dissolving Cu‐In hydrazinium precursor is ascribed to the coordinated S group and strong intramolecular interaction within non‐hydrazine solvents. X‐ray diffraction (XRD) and Raman characterization indicate the formation of the CuIn(S, Se)2 phase after annealing. Through introducing different amounts of excess S/Se, the ratio between CuInS2 and CuInSe2, as well as the morphology of the resulted CuIn(S, Se)2 film can be controlled. Optimized devices exhibit a power conversion efficiency of 3.8% with a CISS absorber layer of only around 300 nm thickness, which is comparable to N2H4‐based devices of similar thickness.